ZN Games Model To Enhance Long Jump Skill For Junior High School Students - Zihan Novita Sari; Arief Darmawan; Qorry Armen Gemael; Putri Cicilia Kristina (Universitas PGRI Palembang, 2021)
AbstractThis study aims to determine the improvement of long jump skills by applying the ZN Games model for junior high school students in Palembang. This research was conducted at a junior high school in the city of Palembang. The experimental method used one group's pre-test-post-test design. The sample of students consisted of 40 junior high school students in Palembang City. The data analysis technique is the paired and unpaired t-test analysis technique at the level of confidence α = 0.05. The results of this study indicate that there is an increase in learning outcomes of long jump skills with the application of the ZN game model. Games, Where the t value = 13.05> t table2.021 and the significance value 0.00 <0.05 (2). There is an increase in long jump skills with the ZN game model giving treatment Games. Where the t value = 13.05> t table 2.021 and a significance value of 0.00 <0.05 (3). There is a difference between students who are given treatment and groups of students who are not given treatment towards increasing long jump skills. The learning method using the ZN Games game model is more effective for improving long jump skills. Where the value of t count = 33.471 and ttable 2.021 and a significance value of 0.00 <0.05.Keywords: ZN Games, Long Jump.